PENERAPAN PEMBELAJARAN METODE JIGSAW UNTUK MENGEMBANGKAN KEMAMPUAN INTERAKSI SOSIAL DALAM PENDIDIKAN ANAK USIA DINI - May Adelin Simanjuntak; Hoerniasih, Nia; Muis, Abdul (Comm-Edu (Community Education Journal), 2025)
Children's social interactions have a very important influence on children's development, because social interactions in early childhood are the foundation for developing social skills, communication and cooperation. With this journal, the researcher aims to examine the importance of children's social interactions in early childhood education through a case study at PAUD Anggrek Kelapa Dua Wetan, East Jakarta. Researchers will observe how children's social interactions develop in the school environment and the surrounding environment by implementing the jigsaw method of learning by teachers. The methods used in this research are observation, interviews and documentation studies. During the research, children's interactions with teachers and peers will be observed and recorded. Interviews as supporting data will be conducted with PAUD heads, teachers and parents to obtain more information regarding the success of implementing jigsaw learning to develop children's social interaction skills. Data from observations and interviews will be analyzed to see the results of applying this method. The results of this research show that the jigsaw method of learning can develop the social interaction skills of early childhood. Not only that, young children can develop social, communication and cooperation skills both in the school environment and in the surrounding environment.